2012
DOI: 10.1111/j.2047-2927.2012.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of testis‐specific kinases TSSK1B and TSSK2 in primates

Abstract: SUMMARYThe testis-specific serine/threonine protein kinases TSSK1 and TSSK2 are known to be essential for male fertility, in mice. The enzymes are present in elongating spermatids, and targeted deletion of the two genes Tssk1 and Tssk2 results in dysregulation of spermiogenesis. The mouse genes are genetically closely linked, forming a Tssk1-Tssk2 tandem. In human, TSSK1 is present in the form of a pseudogene, TSSK1A, which is linked to an intact TSSK2 gene, and in the form of an intact gene, TSSK1B, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
3
19
0
Order By: Relevance
“…Further experiments are needed to assay possible conserved functional roles [ 109 , 110 ] of the homologues identified here. Importantly, we found that our results were consistent with previous homology relationships described for 22q11.2DS genes (e.g., PRODH [ 111 ], UFD1L [ 112 ], DGCR6 [ 113 ], MED15 [ 114 ], TSSK2 [ 115 ], and TXNRD2 [ 116 ]). Using these methods, we identified multiple putative homologues for individual 22q11.2 deletion region genes in the zebrafish, possibly related to gene duplication [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…Further experiments are needed to assay possible conserved functional roles [ 109 , 110 ] of the homologues identified here. Importantly, we found that our results were consistent with previous homology relationships described for 22q11.2DS genes (e.g., PRODH [ 111 ], UFD1L [ 112 ], DGCR6 [ 113 ], MED15 [ 114 ], TSSK2 [ 115 ], and TXNRD2 [ 116 ]). Using these methods, we identified multiple putative homologues for individual 22q11.2 deletion region genes in the zebrafish, possibly related to gene duplication [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…ApTssk1 is grouped together with all mollusk Tssk1 genes of referred species, indicating they have a close genetic distance and may have evolved from the same ancestor (Shang et al 2013). These results strongly suggest that ApTssk1 is a member of the Tssk1 subfamily.…”
Section: Downloaded By [University Of Lethbridge] At 16:20 11 June 2016mentioning
confidence: 76%
“…Tssk1, a member of the highly conserved Tssk gene family widely reported to participate in spermatogenesis (Tanaka & Baba 2005), plays an important role in spermatid differentiation into morphologically mature spermatozoa in mammals (Shang et al 2009(Shang et al , 2013. Some studies have shown that Tssk1 is only expressed in the testis of humans and mice (visconti et al 2001;Li et al 2011;Yang et al 2012).…”
Section: Downloaded By [University Of Lethbridge] At 16:20 11 June 2016mentioning
confidence: 97%
See 1 more Smart Citation
“…A previous analysis of TSKS expression in Tssk1/Tssk2 mutant tubules has shown that TSSK1 or TSSK2 or both are required for the formation of the chromatoid body-derived ring and satellite structures as well as the correct localization of TSKS to these structures during spermiogenesis (Shang et al 2010). Also, recent analysis of the evolutionary history of the Tssk1 and Tssk2 genes in rodents and primates suggests that the two genes may have not completely overlapping functions (Shang et al 2013). One can thus envision a scenario where TSSK1 binds to and phosphorylates TSKS resulting in the localization of TSKS (and TSSK1) to specific puncta in the developing elongating spermatids, whereupon it binds to PPP1CC2, forming, at least transiently, a trimeric (or higher oligomer) complex.…”
Section: Ppp1cc2 Interacts With Tsks and Tssk1mentioning
confidence: 99%